KEKUATAN KARAKTER SANTRI - Fuad Nashori (Millah: Journal of Religious Studies, 2011)
This paper mainly discusses 24 character strengths of students who learn in some Islamic Boarding Schools, particularly their strengths and weaknesses. The object of research was students staying at boarding house and actively studying in some universities of Yogyakarta. Total of respondents was 100 students of 62 males and 38 females. The data analysis was conducted through Value in Action– Inventory Strength method (VIA-IS). The result shows that five strong characters possessed by students were gratitude, kindness, citizenship, fairness and hope. On the other hand, their weakest ones were self regulation, bravery, creativity, perspective and sense of humor.